ROOT SYSTEM OF PASSION FRUIT PLANT IRRIGATED SUBMITED AT DIFFERENTS POTASSIUM LEVELS - FREITAS, Cley Anderson Silva de; COSTA, Carlos Alexandre Gomes; BEZERRA, Francisco Marcus Lima; MONTENEGRO, Afrânio Arley Teles; TEIXEIRA, Adunias dos Santos (Scientia Agraria, 2009)
The spatial distribution of the root system of passion fruit subjected to potassium levels of 150, 300, 450, 600 kg of K2O ha-1 and a control plot all drip irrigated was evaluated in the Vale do Curu - Ceará, in a “Neossolo Fluvico” type of soil. The root system was evaluated 420 days after the transplanting. Digital images were taken in a soil profile and the software SIARCS® applied to analyze them. The distribution and length of the root system were evaluated in the soil profile. In all the potassium levels the crop presented a superficial root system, in way that 80% of the roots concentrated up to 0.40 m in depth. There was a positive interaction relation between the increasing level of potassium applied and the development of roots in the plant, although the effective root depth was not affected by the level of potassium applied. It was found the roots are distributed horizontally until a radius of 1.5 m from the plant’s stem. That distance is thus recommended for installation of moisture sensors when applied to monitor irrigation and fertigation.